Pemberdayaan Pendidikan Dalam Mengantisifasi Permasalahan Kehidupan Masyarakat Modern - Panji Ahmad Syuhada; Syahbuddin . (STAI Hubbulwathan Duri, 2017)
demands, suggestions) by the subject of education to the development of the soul (mind, feeling, willingness and intuition) and the body of the object students with certain materials, at certain time, with a particular method with tools the existing equipment to the creation of a particular person with evaluation according to the teachings of Islam, therefore, the goal of Islamic education is inseparable from the purpose of human life in Islam; creating a personal servant of God who always cautious of Him, and can achieve a happy life in the world and in the heart. In this socio-societal context, these pious nations and personalities can be a blessing of Lil Alamin, both small and large. The purpose of human life in Islam is what can be called as the ultimate goal of Islamic education.Thus,